2021
DOI: 10.1038/s41467-021-22442-3
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular trafficking of Notch orchestrates temporal dynamics of Notch activity in the fly brain

Abstract: While Delta non-autonomously activates Notch in neighboring cells, it autonomously inactivates Notch through cis-inhibition, the molecular mechanism and biological roles of which remain elusive. The wave of differentiation in the Drosophila brain, the ‘proneural wave’, is an excellent model for studying Notch signaling in vivo. Here, we show that strong nonlinearity in cis-inhibition reproduces the second peak of Notch activity behind the proneural wave in silico. Based on this, we demonstrate that Delta expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Additionally, we showed that the onset of the second Notch activation in NBs regulates neuronal cell fate decisions. These findings demonstrate the molecular mechanism of cis -inhibition of Notch signalling and the biological importance of the complex activation mechanism of Notch signalling in neurogenesis [ 104 ].…”
Section: Notch Function In Optic Lobe Developmentmentioning
confidence: 86%
See 3 more Smart Citations
“…Additionally, we showed that the onset of the second Notch activation in NBs regulates neuronal cell fate decisions. These findings demonstrate the molecular mechanism of cis -inhibition of Notch signalling and the biological importance of the complex activation mechanism of Notch signalling in neurogenesis [ 104 ].…”
Section: Notch Function In Optic Lobe Developmentmentioning
confidence: 86%
“…In Su(H) or Delta mutant clones, the proneural wave progression is accelerated [ 98 ]. The second Notch activation in NBs regulates the expression of temporal transcription factors in NBs, which defines the neuronal subtype specification [ 104 ]. EGFR signalling is activated in the wavefront and induces NB differentiation ( Figure 3b , c) [ 98 ].…”
Section: Notch Function In Optic Lobe Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the Notch signal is activated at the wave front of the proneural wave to repress its progression, it is activated again in NBs behind the proneural wave. Interestingly, the second peak of Notch activation coincides with Klu expression and upregulates its expression ( Figure 2b ) [ 62 ]. Similarly, Notch signalling controls the expression of Slp in medulla NBs [ 50 ].…”
Section: Temporal Patterning Following the Proneural Wave In The Larv...mentioning
confidence: 99%